Controlled Synthesis of N‐Doped Carbon Nanospheres with Tailored Mesopores through Self‐Assembly of Colloidal Silica. (22nd October 2015) - Wang, Gang; Sun, Yuhan; Li, Debao; Liang, Hai‐Wei; Dong, Renhao; Feng, Xinliang; Müllen, Klaus
Abstract: Limited strategies have been established to prepare monodisperse mesoporous carbon nanospheres (MCNs) with tailored pore sizes. In this work, a method is reported to synthesize MCNs by combining polymerization of aniline with co‐assembly of colloidal silica nanoparticles. The controlled self‐assembly behavior of colloidal silica enables the formation of uniform composite nanospheres and convenient modulation over mesopores. After carbonization and removal of sacrificial templates, the resultant MCNs possess tunable mesopores (7–42 nm) and spherical diameters (90–300 nm), as well as high surface area (785–1117 m 2  g −1 ), large pore volume (1.46–2.01 cm 3  g −1 ) and abundant nitrogen moieties (5.54–8.73 at %). When serving as metal‐free electrocatalysts for the oxygen reduction reaction (ORR), MCNs with an optimum pore size of 22 nm, compared to those with 7 and 42 nm, exhibit the best ORR performance in alkaline medium.